Characterization of CT scans of patients with Birt-Hogg-Dubé syndrome compared with those of Chinese patients with non-BHD diffuse cyst lung diseases - Wenshuai Xu; Zhiyan Xu; Yaping Liu; Yongzhong Zhan; Xin Sui; Ruie Feng; Min Peng; Xue Li; Jun Wang; Shuzhen Meng; Li Wang; Xinlun Tian; et al. (Orphanet Journal of Rare Diseases, 2020)
Abstract Background and objective The purpose of this study was to create a practical CT-based algorithm to differentiate Birt-Hogg-Dubé (BHD) syndrome from other diffuse cystic lung diseases (DCLD). Methods The study was a retrospective review of the CT images of 33 patients with BHD syndrome, 33 patients with LAM, and 23 patients with NBNL (non-BHD and non-LAM) among DCLD patients. On the basis of the data collected, the CT images were reviewed again to evaluate the characteristics (size, number, distribution, and morphology) of pulmonary cysts. Results Lower lung-predominant cysts were more likely to be found in patients with BHD syndrome than in patients with LAM or in the NBNL DCLD group. In the axial distribution, 18 of 33 patients in BHD group had cysts that were predominantly near the mediastinum, and all the patients in the LAM and NBNL DCLD groups had diffuse cysts. The appearance of fusiform cysts was more easily observed in patients in the BHD group. In total, 58% patients in the BHD group had less than 50 lung cysts, while all patients in the non-BHD group had more than 50 lung cysts. The biggest cyst was located in the lower lobe in 28 of 33 patients in the BHD group, while 11 of 33 patients in LAM group and 10 patients in the NBNL DCLD group had the biggest cyst in the lower lobe. Conclusion The pulmonary cysts in patients with BHD tended to be fusiform, less numerous and located predominantly in the lower lobe and near the mediastinum. These radiologic pulmonary features could assist physicians in differentiating BHD from other DCLDs.